Skeleton crew - King, Stephen, 1947- (New York : G.P. Putnam's Sons, 1985)
n this collection of twenty-two stories, Stephen King takes readers down paths that only he could imagine.
The mist -- Here there be tygers -- The monkey -- Cain rose up -- Mrs. Todd's shortcut -- The jaunt -- The wedding gig -- Paranoid: a chant -- The raft -- Word processor of the gods -- The man who would not shake hands -- Beachworld -- The reaper's image -- Nona -- For Owen -- Survivor type -- Uncle Otto's truck -- Morning deliveries (Milkman #1) -- Big wheels: a tale of the laundry game (Milkman #2) -- Gramma -- The ballad of the flexible bullet -- The reach.
Maine author. Stephen King lives in Bangor, Me. and Florida.
Keywords: Horror tales, American; Horror fiction